Métissage in France: a postmodern fantasy and its forgotten predecents - Yee, J (Carfax Publishing, 2003)
Increasingly in the last decade France has defined its identity in terms of mixity. Its new vocation as a land of métissage is associated with the 'black, blanc, beur' theme of mixed identity. While the old ideal of the universalism of French values is now largely discredited, multiculturalism generally retains a negative association for the French: métissage, instead, is held up as a new ideal, indeed a new universal value. This article comments on the newly fashionable status of métissage by reading it in the context of the older, nightmare vision of racial mixing that dominated from the mid-19th to the mid-20th century. Despite this essentially negative view there were, it is suggested, some precedents for the current attempt at a political recuperation of métissage.